An Integrated Web-Based Monitoring System For Optimizing The Supervision Of Student Internships And Final Projects - Ilyas Ruhiyat; Nita Winda Sari; Adie Kusna Wibowo; Santo Wijaya; Manase Sahat H Simarangkir (Politeknik META Industri Cikarang, 2026)
Background : The implementation of Field Work (PKL)/Internships and Final Projects is an important part of the academic process at universities, requiring ongoing monitoring by academic advisors and academic programs. However, at many universities, the monitoring of these two activities is still conducted through separate platforms, resulting in inefficient data management, disjointed information, and difficulties in comprehensively tracking student progress Purpose : This research aims to develop and implement a web-based monitoring platform that integrates the supervision processes for PKL/Internships and Final Projects into a single system, so that all data, advising activities, progress, and academic documents can be managed centrally Methodology : The system was developed using the Waterfall method, which includes requirements analysis, design, implementation, testing, and maintenance, utilizing the Laravel framework, the PHP programming language, and a MySQL database Findings : System validation was performed through Black Box Testing on 10 test scenarios. Test results showed a 100% success rate for system functionality, meaning all key features operate as intended to meet user needs Implications : The integration of the monitoring processes for internships and final projects into a single platform is the primary contribution of this research, as it enables unified progress monitoring, reduces data management duplication, and provides consistent academic information for all stakeholders. Originality : The system’s implementation offers benefits such as improved efficiency in the monitoring process, ease of tracking student progress in real time, accelerated academic administration, and the provision of more accurate information as a basis for evaluation and decision-making.